Visual communication for smoke-free homes: A community-based health promotion intervention in rural indonesia - Bujawati, Emmi; Haerana, Bs. Titi; Radjiman, Evi Aprianti (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2026)
Although tobacco-control interventions in Indonesia have largely emphasized public smoke-free areas, limited evidence exists on participatory visual communication strategies for reducing cigarette smoke exposure within rural households. This community service program aimed to improve community awareness and encourage the implementation of smoke-free homes through the installation of “Smoke-Free Home” stickers in Kasimburang Village. The program employed a Participatory Action Research approach with a pre–post test without control intervention design, involving initial screening, health education, sticker installation, interviews, and field observations. Respondents’ knowledge increased from a mean score of 9.12 at pre-test to 9.62 at post-test I and 9.81 at post-test II, accompanied by decreasing score variability. Among 26 respondents, reported indoor smoking declined from 88.5% before counseling to 53.8% afterward, while 73.1% reported implementing household no-smoking rules. Field evaluation of 58 households showed that 81.0% of stickers remained installed and 77.6% remained intact and readable. These findings indicate that combining health education with visible household reminders may strengthen awareness, behavioral commitment, and smoke-free home practices. This low-cost, community-based intervention has potential to support protection from secondhand smoke and contribute to the prevention of tobacco-related non-communicable diseases in rural communities.